Prevalence of smoking before and during pregnancy and changes in this habit during pregnancy in Northwest Russia: a Murmansk county birth registry study - Kharkova, Olga Alexandrovna; Krettek, Alexandra; Grjibovski, Andrej; Nieboer, Evert; Odland, Jon Øyvind (Reproductive Health, 2016)
Publisher's version, source: http://doi.org/10.1186/s12978-016-0144-x . BACKGROUND Smoking during pregnancy leads to adverse maternal and birth outcomes. However, the prevalence of smoking among women in Russia has increased from < 5 % in the 1980s to > 20 % in the 2000s. We conducted a registry-based study in Murmansk County, Northwest Russia. Our aims were twofold: (i) assess the prevalence of smoking before and during pregnancy; and (ii) examine the socio-demographic factors associated with giving up smoking or reducing the number of cigarettes smoked once pregnancy was established. METHODS This study employs data from the population-based Murmansk County Birth Registry (MCBR) collected during 2006–2011. We used logistic regression to investigate associations between women’s socio-demographic characteristics and changes in smoking habit during pregnancy. To avoid departure from uniform risk within specific delivery departments, we employed clustered robust standard errors. RESULTS Of all births registered in the MCBR, 25.2 % of the mothers were smokers before pregnancy and 18.9 % continued smoking during pregnancy. Cessation of smoking during pregnancy was associated with education, marital status and parity but not with maternal age, place of residence, and ethnicity. Women aged ≤ 20–24 years had higher odds of reducing the absolute numbers of cigarettes smoked per day during pregnancy than those aged ≥ 30–34 years. Moreover, smoking nulliparae and pregnant women who had one child were more likely to reduce the absolute numbers of cigarettes smoked per day compared to women having ≥ 2 children. CONCLUSIONS About 25.0 % of smoking women in the Murmansk County in Northwest Russia quit smoking after awareness of the pregnancy, and one-third of them reduced the number cigarettes smoked during pregnancy. Our study demonstrates that women who have a higher education, husband, and are primiparous are more likely to quit smoking during pregnancy. Maternal age and number of children are indicators that ...